2023
DOI: 10.1039/d3sc04532c
|View full text |Cite
|
Sign up to set email alerts
|

Ion sieving membrane for direct seawater anti-precipitation hydrogen evolution reaction electrode

Qianfeng Liu,
Zhao Yan,
Jianxin Gao
et al.

Abstract: In seawater, the severe hydroxide-based precipitation on the hydrogen evolution reaction (HER) electrode surface is still a major stumbling block for direct seawater electrolysis. Here, we design a direct seawater...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Hydrogen energy, as a secondary energy source with abundant sources, and a widely used green and low-carbon fuel, is an important carrier to achieve green transition of energy. [64][65][66][67] Hydrogen production by electrochemical water splitting is an efficient and clean hydrogen production technology, with a simple hydrogen production process and high product purity, which is one of the most promising technologies for large-scale hydrogen production. There have been many articles about GDY/MOs used for HER applications.…”
Section: Applications Of Gdy/mos In Catalysismentioning
confidence: 99%
“…Hydrogen energy, as a secondary energy source with abundant sources, and a widely used green and low-carbon fuel, is an important carrier to achieve green transition of energy. [64][65][66][67] Hydrogen production by electrochemical water splitting is an efficient and clean hydrogen production technology, with a simple hydrogen production process and high product purity, which is one of the most promising technologies for large-scale hydrogen production. There have been many articles about GDY/MOs used for HER applications.…”
Section: Applications Of Gdy/mos In Catalysismentioning
confidence: 99%
“…Simulations and experiments revealed that the positively charged Ni(OH) 2 membrane with nanometer-scale cracks evidently hindered the transfer of Mg 2+ and Ca 2+ while rapidly transferring OH − and H 2 O. The Ni(OH) 2 membrane decorated seawater HER electrode reduced precipitation by about 98.3% and exhibited high activity and stability [63]. Numerous studies have investigated the alkaline OER mechanism using noble metal catalysts [65].…”
Section: Design Principles Of Cathode and Anodementioning
confidence: 99%
“…Hydrogen production through water splitting driven by renewable energy, which does not cause environmental pollution problems, such as carbon emissions, is an important way to produce green hydrogen [3][4][5][6][7][8][9]. Water electrolysis technology usually includes hydrogen evolution reaction (HER) [10][11][12] and oxygen evolution reaction (OER) [13][14][15]. The OER involves a four-electron transfer process, resulting in slow reaction kinetics and high overpotential.…”
Section: Introductionmentioning
confidence: 99%